2023
DOI: 10.3389/fmicb.2023.1228693
|View full text |Cite
|
Sign up to set email alerts
|

Male infertility risk and gut microbiota: a Mendelian randomization study

Zhi-da Fu,
Yao Wang,
Hong-li Yan

Abstract: BackgroundIn recent decades, the decline of male sperm quality has become a worldwide phenomenon, with sperm quality of critical importance for the ability to conceive naturally. Recent studies suggest that male fertility function is closely linked to the gut microbiota, however, the cause-and-effect association between the gut microbiota and male infertility risk is currently unclear.MethodsWe performed one two-sample Mendelian randomization (MR) study, which uses summary data on human gut microbiota from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…The Mendelian Randomization study method is a powerful tool in epidemiological research, utilizing genetic variation as to assess the causal association between risk factors and specific diseases (12). Previous Mendelian Randomization studies (13)(14)(15) found a causal correlation between gut microbiota and male infertility. However, these studies only focused on exploring whether there is a causal relationship between specific gut microbiota and the risk of MI, without investigating the potential mediating factors and mechanisms of disease development between them.…”
Section: Introductionmentioning
confidence: 99%
“…The Mendelian Randomization study method is a powerful tool in epidemiological research, utilizing genetic variation as to assess the causal association between risk factors and specific diseases (12). Previous Mendelian Randomization studies (13)(14)(15) found a causal correlation between gut microbiota and male infertility. However, these studies only focused on exploring whether there is a causal relationship between specific gut microbiota and the risk of MI, without investigating the potential mediating factors and mechanisms of disease development between them.…”
Section: Introductionmentioning
confidence: 99%